GLUCOCORTICOID EXCESS INDUCES NON-DIPPING BLOOD PRESSURE AND RENAL VASCULAR DYSFUNCTION. (April 2021) - Costello, Hannah; Jones, Natalie; Grenier, Celine; Stewart, Kevin; Holmes, Megan; Livingstone, Dawn; Dhaun, Neeraj (Bean); Bailey, Matthew
Abstract: Objective: Blood pressure (BP) abnormalities such as loss/attenuation of nocturnal BP dip (non-dipping) increase cardiovascular risk. The mechanisms underlying non-dipping are not clear, but renal and vascular dysfunction has been implicated. People with abnormal glucocorticoid (GC) homeostasis, such as in Cushing's syndrome, often display non-dipping BP therefore, here we investigated the contribution of GCs to BP rhythmicity. Design and method: The effect of GC excess, driven by ACTH infusion, on BP and plasma GC rhythmicity was examined in adult male C57BL/6J mice. Radiotelemetry was used to measure BP longitudinally before and after ACTH infusion (2.5 mg/day for 14days via minipump). Diurnal plasma GCs was measured by ELISA. Diurnal renal vascular function was investigated ex vivo by wire myography in isolated renal arteries from separate cohorts of mice either control or ACTH-treated collected between 7–8AM (day) or 7–8PM (night). Vascular reactivity to vasoconstrictor phenylephrine (PHE), endothelium-dependent acetylcholine (ACh) and endothelium-independent sodium nitroprusside (SNP) vasodilators was assessed. Data are mean ± SD. Results: After 5days of baseline measurements, 24-hour systolic BP (SBP) was 123.8 ± 4.2 mmHg and 24-hour diastolic BP (DBP) was 96.2 ± 5.6 mmHg. The day:night SBP and DBP variation was 12.8 ± 4.5 mmHg and 12.3 ± 4.8 mmHg, respectively. ACTH-excess increased 24-hour SBP to 133.8 ± 1.7 mmHg and 24-hour DBP to 101.4 ± 2.1 mmHg. The day:night SBP and DBP variation was reduced to 0.6 ± 7.2 mmHg (p = 0.0166) and 2.4 ± 9.6 mmHg (p = 0.0235), respectively. Day:night activity count during BP measurements was similar before and after ACTH infusion. Diurnal plasma GCs was increased following ACTH infusion, compared with baseline (p < 0.0001). Furthermore, ACTH-excess flipped the diurnal rhythm of GC, so the day plasma GC concentration is higher than the night. Day control renal arteries showed a trend for an increase in sensitivity to PHE (p = 0.0578) and SNP (p = 0.0795), with no changes in ACh (p = 0.1299), compared with night control renal arteries. ACTH-excess caused no differences in day and night responses to PHE (p = 0.5526), ACh (p = 0.1169), and SNP (p = 0.9466). ACTH-excess caused renal vascular dysfunction, compared with controls, causing a significant reduction in sensitivity to PHE (p = 0.0005), ACh (p = 0.0128) and SNP (p = 0.0002). Conclusions: These data show that chronic GC induces non-dipping BP and renal vascular dysfunction.